Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1093/jxb/eri216
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deficit irrigation on water use efficiency and carbon isotope composition (δ13C) of field-grown grapevines under Mediterranean climate

Abstract: The objective of this study was to evaluate the effect of deficit irrigation on intrinsic water use efficiency (A/g s ) and carbon isotope composition (d 13 C) of two grapevine cultivars (Moscatel and Castelã o), growing in a commercial vineyard in SW Portugal. The study was done in two consecutive years (2001 and 2002). The treatments were full irrigation (FI), corresponding to 100% of crop evapotranspiration (ETc), rain-fed (no irrigation, NI), and two types of deficit irrigation (50% ETc): (i) by supplying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
64
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 26 publications
17
64
1
2
Order By: Relevance
“…The >3.00 per mil difference in δ 13 C observed between juice of RR and NRR vines is a relatively large treatment separation compared to published studies with grape (Gómez-Alonso and García-Romero 2010). As did other studies (Chaves et al 2007, de Souza et al 2005, we found greater amplitude of treatment effects on δ 13 C with berry juice than with leaf laminae. In the latter case, the midshoot leaves that we sampled had fully developed by bloom and their structural carbon was essentially fixed at that point.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The >3.00 per mil difference in δ 13 C observed between juice of RR and NRR vines is a relatively large treatment separation compared to published studies with grape (Gómez-Alonso and García-Romero 2010). As did other studies (Chaves et al 2007, de Souza et al 2005, we found greater amplitude of treatment effects on δ 13 C with berry juice than with leaf laminae. In the latter case, the midshoot leaves that we sampled had fully developed by bloom and their structural carbon was essentially fixed at that point.…”
Section: Discussionsupporting
confidence: 88%
“…The δ 13 C values reported here are similar to those determined in studies where water availability to grapevines was regulated to impose a range of water stress (Chaves et al 2007, de Souza et al 2005 or where natural soil types afforded a range of plant available water levels (Van Leeuwen et al 2009). While RR caused a pronounced reduction in the discrimination against 13 C, UTCC did not.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, Bainskloof was also the site where species had high WUE, again indicating it as a more drought-stressed environment, despite its intermediate stream flow regime. A similar result was found with Vitis vinefera where some sites were significantly more water-use efficient than others, promoted by a deficit in water availability (De Souza et al 2005).…”
Section: Dutoitskloofsupporting
confidence: 81%
“…The volumetric water content of the soil shows significant differences among treatments, especially in 2010 and 2012, although the degree of soil moisture does not entirely conform to the degree of stress on the Soil-plant water stress integral and relationships with productivity S Ψ is presented as a useful tool for differentiating among treatments for any of the variables studied (Table 4), which is consistent with the results of De Souza et al (2005) in cvs. 'Moscatel' and 'Castelão' and Ginestar et al (1998a,b) in cv.…”
supporting
confidence: 81%
“…He established a methodology for assessing the cumulative effect of water deficit (WD) on the stress-intensity of crops through the 'water stress integral' (S Ψ ). The application of this method to Vitis vinifera (L.) evaluates the effects of water stress on production and the relationship of water stress to vine-water status indicators (Ginestar et al, 1998a,b;De Souza et al, 2005;Salón et al, 2005;De la Hera et al, 2007;Martínez et al, 2007, Dayer et al, 2012. Baeza et al (2007) consider that S Ψ provides a faster method and may be a good parameter for explaining the long-term response of vines to water deficit with relation to yield or must composition.…”
Section: Experimental Conditionsmentioning
confidence: 99%